1984
DOI: 10.1177/000331978403501107
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Modulus in Young Diabetic Patients (Ultrasound Measurements of Pulse Wave Velocity)

Abstract: Aim of this study is to confirm the validity of non-invasive evaluation with Doppler C.W. in the study of arterial diseases and in the identification of pre-clinical arterial lesions. We studied twenty-eight children suffering from diabetes mellitus, and dependent on insulin and a control group composed of twenty-eight healthy persons. All subjects were studied using the methodology of the transit time for the determination of the elastic modulus of the lower limb arterial wall and results were analysed accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…The bulk of the available PWV research in pediatric subjects includes those with diseases such as type 1 diabetes mellitus, 177,178 neurofibromatosis, 179,180 primary snoring, 181 Kawasaki disease, 182 polyarteritis nodosa, 183 and coarctation of the aorta after surgical repair. 184 -186 Most of these studies have control groups of varying mean ages (5 months to 22 years), with patient numbers ranging from 28 to 155 subjects.…”
Section: Data In Children and Adolescentsmentioning
confidence: 99%
“…The bulk of the available PWV research in pediatric subjects includes those with diseases such as type 1 diabetes mellitus, 177,178 neurofibromatosis, 179,180 primary snoring, 181 Kawasaki disease, 182 polyarteritis nodosa, 183 and coarctation of the aorta after surgical repair. 184 -186 Most of these studies have control groups of varying mean ages (5 months to 22 years), with patient numbers ranging from 28 to 155 subjects.…”
Section: Data In Children and Adolescentsmentioning
confidence: 99%
“…The literature consistently reports increased aortic stiffening with diabetes, 5,6 as well as less extreme alterations in glucose metabolism. 8,9,11 Our data support this finding, with glycosylated hemoglobin being a strong independent predictor of higher aPWV.…”
Section: Discussionmentioning
confidence: 93%
“…The cardiovascular risks associated with systolic hypertension are well documented. 3,4 Accelerated arterial stiffness has been linked to diabetes, 5,6 hyperglycemia, hyperinsulinemia, and impaired glucose tolerance. [7][8][9][10][11] These findings have been confirmed in older adults 12 and suggest that insulin resistance or its products, ie, hyperglycemia and hyperinsulinemia, may promote arterial stiffening independent of age.…”
mentioning
confidence: 99%
“…30 The findings presented here are consistent with this relationship and suggest that prevention of vascular stiffness will improve the health of older adults. The primary risk factors for vascular stiffness are hypertension [31][32][33][34] ; glucose abnormalities, including diabetes, 35,36 hyperglycemia, hyperinsulinemia, and impaired glucose tolerance [37][38][39] ; and increased body fat, specifically visceral adipose tissue. 12,40 In Health ABC participants, we have reported that all markers of central fat, including visceral and intermuscular and intramuscular fat, are associated with a higher PWV.…”
Section: Sutton-tyrrell Et Al Pwv Predicts CV Events In Older Adults mentioning
confidence: 99%